THE IMPORTANCE OF URBAN LANDSCAPING - D.S. Toshpulatova, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Expanding the assortment of plant species used in urban landscaping and cultivating native flora species adapted to local conditions are of great importance. Uzbekistan‟s flora boasts numerous ornamental plants. Identifying, studying, and introducing wild ornamental plants into urban landscaping is one of the pressing issues of today.